The effects of teachers' using the Picture Word Inductive Model on young language learners vocabulary retention - Nguyễn Thị Yến Duy (Trường Đại học Trà Vinh, 2024)
The objectives of the research are to help EFL (English as a Foreign Language) YLLs improve vocabulary learning and retention over time and to foster their positive attitude through the PWIM.